2013
DOI: 10.1021/jo302460d
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-Catalyzed Synthesis of 3,3-Spirocyclopenteneoxindoles from γ-Substituted Allenoates: Systematic Studies and Targeted Applications

Abstract: The phosphine-promoted [3 + 2] cyclizations between γ-substituted allenoates and arylideneoxindoles have been applied to the stereoselective synthesis of spiro(cyclopentene)oxindoles with trisubstituted cyclopentene units. It has been demonstrated that PPh(3) operates a very efficient control of the relative stereochemistry of the three stereogenic centers of the final spiranic products. Focused experiments have been carried out then so as to access carbocyclic analogues of an important series of anticancer ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 53 publications
0
39
0
Order By: Relevance
“…In the authors' early reports, it was found that a phosphane-catalyzed [3 + 2] annulation preferentially occurred for δ-alkyl-substituted penta-2,3-dienoates with analogous 3-arylideneoxindoles. [44] Scheme 49. Phosphane-catalyzed [4 + 2] annulation of γ-substituted allenoates with 3-arylideneoxindoles.…”
Section: Annulations Involving γ-Substituted Allenesmentioning
confidence: 99%
“…In the authors' early reports, it was found that a phosphane-catalyzed [3 + 2] annulation preferentially occurred for δ-alkyl-substituted penta-2,3-dienoates with analogous 3-arylideneoxindoles. [44] Scheme 49. Phosphane-catalyzed [4 + 2] annulation of γ-substituted allenoates with 3-arylideneoxindoles.…”
Section: Annulations Involving γ-Substituted Allenesmentioning
confidence: 99%
“…Both phosphahelicenes (P)-1 and (P)-3 afforded the cyclopentene 11 a as the unique [3+ +2] cyclization product, which results from the a-addition of the allenoate to the olefin (Michaeltype addition of the allenoate through its a-carbon atom). [16] The syn-isomer was formed preferentially with greater than 95:5 diastereomeric ratio.T he use of (P)-1 as the catalyst provided 11 a in am oderate 30 %y ield with ah igh ee value (entry 1). Gratifyingly,t he same product 11 a could be obtained in much higher enantiomeric excess (95 % ee)a nd 37 %y ield, by using the newly synthesized (P)-3 as the catalyst (entry 2).…”
Section: Methodsmentioning
confidence: 97%
“…Noteworthy is that the reaction also proceeds with challenging substrates such as alkyl-substituted dicyanoolefins,albeit with some decrease in enantioselectivity (82 % ee for R 1 = cyclohexyl, entry 14). Several g-substituted allenes could be used, thus giving excellent yields and enantioselectivities,w ith up to 97 % ee obtained with the phenyl-substituted allene (entries [15][16][17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…29 The first key point in this study was to establish the regioselectivity of the cyclization process, since γ-substituted allenoates or the corresponding alkynes, are known to react with enones giving the α-adduct as the major product. 30 As a model reaction, we considered the Ph 3 P-catalyzed [3+2] cyclization between (E)-1-acetyl-3-benzylideneindolin-2-one and ethyl 4-phenylbuta-2,3-dienoate (Scheme 31, entry 1).…”
Section: Scheme 29 Ferrophane-catalyzed Synthesis Of Phosphonate-subsmentioning
confidence: 99%